A Clinical Case of Patient Carrying Rare Pathological PSEN1 Gene Mutation (L424V) Demonstrates the Phenotypic Heterogenity of Early Onset Familial AD - Stoychev, Kaloyan R.; Stoimenova-Popova, Maya; Chumpalova, Petranka; Ilieva, Lilia; Swamad, Mohamed; Kamburova-Martinova, Zornitsa (Frontiers in Psychiatry, 2019)
Dementia comprises several neurodegenerative disorders sharing common neuropsychiatric features and Alzheimer’s disease (AD) is the most common of them. Genetic factors are strongly implicated into its etiology especially for early-onset cases (EOAD) with symptoms occurring before the age of 65. About 10% of these are inherited in autosomal dominant fashion via pathogenic polymorphisms in three genes – APP, PSEN-1 and PSEN-2. Despite this genotypic clarity however, a remarkable phenotypic variability exists with different symptom constellations observed in patients with identical mutations. Below we present a case of a 39-year-old male with a family history for early onset dementia who was referred to our department with history for abrupt behavioral change 7 months prior to hospitalization – noticeable slowing of speech and reactivity, impaired occupational functioning and irritability, followed by aphasic symptoms and transient episodes of disorientation. He was followed up for two years and manifested rapidly progressing cognitive decline with further deterioration of speech, apraxia, acalculia, ataxia and subsequently bradykinesia and tremor. Based on the clinical and neuroimaging findings (severe cortical atrophy), familial EOAD was suspected and a whole exome sequence (WES) analysis was performed. It identified a heterozygous missense variant Leu424Val (g.71074C>G) in PSEN-1 gene considered to be pathogenic, and to our knowledge, only been reported once until now in a Spanish female patient. Despite genotype identity however, profoundly distinct phenotypic presentations were observed in the two patients, along with a difference in neuroimaging findings, and the presence and absence of seizures in the Spanish and Bulgarian case, respectively. Besides, two other “typical” PSEN-1 associated EOAD clinical features were absent - myoclonus and spastic paraparesis. Age of onset of symptoms was consistent with most of the other reported mutations affecting the same codon of PSEN-1 gene. In addition, our patient had co-occurring lupus erythematosus (LE) and we suggest that this condition might be etiologically linked to the PSEN-1 mutation. In addition to illustrating the symptomatic heterogeneity of PSEN1 caused EOAD, our study confirms that in patients presenting with cognitive deterioration and positive family history for dementia, WES can be especially informative and should be considered as a first-line examination.